Clinical and Echocardiographic Outcomes of Transcatheter Tricuspid Valve Interventions: A Systematic Review and Meta-Analysis - Sannino, Anna; Ilardi, Federica; Hahn, Rebecca T.; Lancellotti, Patrizio; Lurz, Philipp; Smith, Robert L.; Esposito, Giovanni; Grayburn, Paul A. (Frontiers in Cardiovascular Medicine, 2022)
Background. Medically-managed tricuspid regurgitation (TR) has detrimental outcomes. Transcatheter tricuspid valve interventions (TTVI) represents an alternative to surgery in high-risk patients, however only early experiences exist. Aims. Analyze the clinical and echocardiographic outcomes of TTVI. Methods. MEDLINE, ISI Web of Science and SCOPUS databases were searched for studies published up to June 2021. Studies reporting data on outcomes post-TTVI were included. The study was designed according to PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) requirements. The primary endpoint was all-cause mortality at 30-day and 1-year post-TTVI. Results. Out of 2718 studies, 27 were included. 30-day and 1-year all-cause mortality were 5% (95% Confidence Interval [CI]: 4% to 8%, p<0.001) and 25% (95% CI: 12% to 45%, p=0.016). Procedural success was associated with a 58% risk-reduction in 1-year mortality vs lack thereof (Odds Ratio 0.42, 95% CI: 0.27 to 0.66, p<0.001). TTVI is associated with a significant reduction in TR severity (TR EROA, mean difference [MD] 0.31 cm2; 95% CI: 0.23 to 0.39 cm2, p<0.001; regurgitant volume, MD 23.54 ml; 95% CI: 17.4 to 29.68 ml, p=0.03) and increase in forward stroke volume (FSV, MD 3.98 ml; 95% CI: 0.11 to 7.86 ml, p=0.04). Conclusions. TTVI significantly reduces TR severity and increases FSV, and is associated with improved survival at 1-year compared to patients without procedural success. Long-term outcomes compared to medical therapy await the results of on-going pivotal trials, nonetheless TTVI appear to be a promising alternative to surgery for TR.